Hubungan Kelas Antenatal Mengenai Program Perencanaan Persalinan Dan Pecegahan Komplikasi Dengan Kesiapan Persalinan Ibu Hamil Trimester III - Ni Putu Gita Arneni; Ni Nyoman Sumiasih; Juliana Mauliku (Poltekkes Kemenkes Denpasar, 2019)
Maternal death during birth is a preventable tragedy through the birth preparation with antenatal class programs and birth planing and prevention of birth complication programs (P4K). The purpose of this study to know the relation between antenatal class about P4K with third trimester pregnant woman birth preparedness. Study design used is analytic survey with cross sectional approach. Research was conducted at North Denpasar PHC on May 5-June 2 2018 with 51 third trimester pregnant women as respondents. Normality test data used Kolmogorov-Smirnov and statistical testing using Chi-square test. Based on data, 66,7% of the sample did not attend the antenatal class and 33,3% sample attend the antenatal class. On samples that did not attend the antenatal class, most of them (55,9%) not well-prepared. On samples that attend the antenatal class, most of them (76,5%) were prepared well to face delivery. The participation of the antenatal class about P4K and birth preparedness were related significantly (p value 0,0290,05). Antenatal class can increase knowledge, skilss and motivation to preparing birth through P4K. It is necessary to improve the quality of the antenatal class implementation to the pregnant woman to preparing birth based on birth planing and prevention of birth complication programs.Keywords: Antenatal Class; P4k; Birth Preparedness